Development of Android-Based Learning Media in Information Communication Technology (ICT) at Senior High School - Indah, Indah Rahmatika Sari; Effendi, Hansi; Lapisa, Remon; Wulansari, Rizky Ema (The Indonesian Journal of Computer Science, 2023)
Android-based learning media is one of the media that is easy to use by teachers and students in achieving learning objectives. This study aims to produce valid, practical, and effective learning media used for learning. The method used is Research and Development (R&D) with a 4-D development model (four D models). This study used an instrument in the form of a questionnaire. The questionnaires were divided into validation questionnaires, practicality, and effectiveness questionnaires. For data analysis, researchers used Aiken's formula and Gain Score. The validation sheet is filled out by 4 validators consisting of 2 material validators and 2 media validator. The practicality sheet is filled out by 30 students and 2 teacher. For effectiveness data used questions filled out by students. The questionnaire data obtained a validity level of 0.95 which indicates that the developed media is valid. For practicality, the result is 90% with the very practical category. The effectiveness of the developed media is seen from the value of students. After using the media, 100% of students had scores above the KKM, while from the gain score test, they got a value of 0.75 which means that the learning media developed can be said to be effective. Based on these data it can be concluded that android-based learning media in Information and Communication Technology (ICT) subjects is valid, practical, and effective for use as learning media.